The seafood industry : species, products, processing and safety - Flick, George J.; Granata, Linda Ankenman; Martin, Roy E. (Wiley-Blackwell, 2012)
The Seafood Industry: Species, Products, Processing, and Safety, Second Edition is a completely updated and contemporary revision of Flick and Martin's classic publication, The Seafood Industry